Use of ASI thresher helps 45,600 rice farmers to accees more credit to expand and intensify rice production in Senegal - CGIAR Research Program on Rice (2020)
We examine whether the adoption of the ASI thresher technology by rice farmers in the Senegal River Valley increases their access to credit and their creditworthiness through various pathways. The results show that ASI rice thresher adopters borrowed more money (between USD 388 and 864) per season in comparison to their neighbours who had not adopted the ASI thresher.